Eksplorasi dan Karakterisasi Bakteri Agens Hayati dari Imperata cylindrica untuk pengendalian Rigidoporus microporus - Tatit Sastrini; Mochamad Yadi Nurjayadi; abdul munif (Jurnal Fitopatologi Indonesia, 2019)
Exploration and Characterization of Biological Agents Bacteria from Imperata cylindrica for Controlling Rigidoporus microporusWhite root disease caused by Rigidoporus microporus is an important disease in rubber plantation. This pathogen causes damage to roots, thus adversely affect plant growth and productivity of rubber plantation. Therefore controling of this pathogen is important to do. The objective of this research was to obtain biological agents bacteria from the various parts of alang-alang (Imperata cylindrica) which have inhibitory activity against the growth of R. microporus The research was conducted through exploration of biological agents from the various parts of alang-alang, antibiosis activity test, and characterization of potential isolates. Based on antibiosis activity test, seven isolates (Rph 7, Rph 8, Rph 15 Rph 17, 15, E47, and isolate 47) showed antibiosis activity against R. microporus. Suppression activity of R. microporus growth by seventh of potential isolates ranged between 26.7-58.9%. The highest inhibition was demonstrated by isolate 47 suspected leaf endophytic bacteria. Seventh of potential isolates are Gram-positive bacterial that can form spores. The biological agen’s bacterial dominated by isolates from the reeds rhizosphere. This result indicates that rhizosphere is a potentialy source in the exploration of biological agents. In addition, R. microporus is a soil-borne pathogen which colonizes the roots therefore exploration from rhizosphere samples allows obtaining potential biological agents.